EFFECTIVENESS OF JIGSAW TYPE COOPERATIVE LEARNING MODEL AND NUMBERED HEAD TOGETHER LEARNING MODEL ON MATHEMATICS LEARNING OUTCOMES IN CLASS VII MTs MUHAMMADIYAH KARANGKAJEN - Zumrotun Mukaffah; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was conducted with the reasons student low mathematic result learning, are less active in learning, rare and shy to ask. Math as a difficult subject and learning model used by teachers less varried. This study aims to determine the effectiveness of cooperative learning model NHT, learning models jigsaw and the result learning mathematic in second grade MTs Muhammadiyah Karangkajen in first semester academic year 2016/2017. The population in this study were all students of class VII MTs Muhammadiyah Karangkajen in first semester of academic year 2016/2017 is divided into five classes totaling 150. Samples were taken 3 classes using random sampling techniques, derived  class VII D as an experimental class I, VII C class as the experimental class II, and VII A class as the control class. Data analysis techniques used for the prerequisite test including normality test with chi-square formula, bartlett homogeneity test by test, and test hypotheses include F test and significant raced different (LSD). Results of research on the significant level of 5% and db (2,87) show (1) there are differences in result learning of mathematics that uses model jigsaw, NHT learning model and conventional learning model. It is indicated with Fcount = 9,7078 > Ftable = 3,115 and (2) Cooperative learning NHT, jigsaw and more effective than conventional towards mathematics learning result. These results indicated by result of hypothesis testing 1-SD where the significant level of 5% and 87 degress of freedom is obtained in one case because of  then  accepted means . In case II  then  is rejected and > means , while in the case III   then  is rejected and dan  > means .